Factors Related to Maternal Readiness at Telehealth in Prenatal Care in Rural Areas of Indonesia - Mulyati, Sri; Purwaningsih, Dewi; Resmana, Rika; Sariaty, Saur (Gaceta Médica de Caracas, 2023)
Introduction: Pregnancy is a physiological process, but if not managed properly it could become pathological. Telehealth is the use of information and telecommunications technology to support prenatal care. This study aimed to determine the factors related to maternal readiness at Telehealth Prenatal care in rural areas of Indonesia. Methods: This research method was a crossectional study. The respondents were 65 pregnant women in rural areas in Indonesia. Sampling was done with quota sampling. The variables of this study were the Readiness Factor and Readiness for Prenatal Telehealth. The data were analyzed using univariate data using frequency distribution and bivariate using the Chi-Square test.